Workplace violence, post-traumatic stress disorder symptoms, and personality. (1st January 2021) - Jankovic, M.; Sijtsema, J.J.; Reitz, A.K.; Masthoff, E.D.; Bogaerts, S.
Abstract: Patient violence against staff members in forensic psychiatric institutions is highly prevalent. To date, little is known about individual characteristics that increase the likelihood of being victimized. Therefore, the current cross-sectional study was designed to investigate the extent to which staff members' Post-Traumatic Stress Disorder (PTSD) symptoms and the Big Five personality traits are linked to perceived patient violence. Moreover, it was investigated to what extent staff members' personality affected the association between PTSD symptoms and perceived workplace victimization. Data were obtained from 353 staff members in forensic psychiatric institutions (51.8% female, age, M  = 42.4, SD  = 12.1). Regression analyses showed that lower levels of emotional stability and higher reports of PTSD symptoms were associated with experiencing more verbal patient violence, whereas lower levels of openness and higher levels of extraversion were associated with experiencing more physical patient violence. Personality moderated the association between PTSD symptoms and physical victimization with the association being stronger for individuals with higher levels of conscientiousness and lower levels of agreeableness. These findings provide useful information for tailoring interventions in clinical practice aimed at reducing the risk of patient-staff violence.